Penguatan Tata Kelola Desa Wisata Melalui Pemberdayaan Kelompok Sadar Wisata (POKDARWIS) Tolokan Telomoyo Kabupaten Semarang - Haura Tabriza Asyan; Izza Ulumuddin Ahmad Asshofi; Muhammad Askha Rafliansyach Wijaya; Nabilla Dinda Ramadani; Anasthasia Indah Larasati; Dian Mita Amanda; Zahra Khoironi Aulia; Dinar Visita Dewi Anggraeni; Fresta Indah Lestari; Ariel Sabella Siva Shan; Genta Bernard Mahardika (Pusat Riset dan Inovasi Nasional, 2024)
Tolokan Village, which is located at the foot of Mount Telomoyo, has advantages in its natural potential. The natural potential found in the village includes the agricultural sector which has an impact on tourism. Tolokan Village is pioneering a tourism village initiated by the Tourism Awareness Group (POKDARWIS) but its role in tourism awareness has not been optimal so that community participation is still low in exploring the potential of the tourism village. The natural potential of Tolokan Village has not been managed in a structured manner due to the lack of understanding and provision of its management. The purpose of writing this article is to describe the process of strengthening tourism village governance with the Tolokan Telomoyo Tourism Awareness Group (POKDARWIS) in collaboration with the Association of Hospitality Management Students of Universitas Dian Nuswantoro. The method used in this article is descriptive qualitative by conducting participatory training, discussion, packaging tour, and field practice carried out to empower village community in fostering governance Tourism Awareness group. In doing so, it can realize Sapta Pesona as a support in pioneering tourism villages. The result of this village community service is product of a set of tour packages, a tour guide group, a roadmap for developing a tourism village for the next 3 years so that the potential of Tolokan village can be explored and provide added value to local residents, the formation of synergy between Universitas Dian Nuswantoro, the Tolokan Tourism Awareness Group (POKDARWIS), the Tolokan Women Farmers Group (KWT), and villagers in preparing a structured tourism village pilot.